PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN DESA WISATA TANJUNG BALAM KECAMATAN SIAK HULU KABUPATEN KAMPAR - Harbimas, Abeltran; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Tourism can provide opportunities for people to market their products, such as small businesses such as handicrafts, leather, woven goods, cosmetics and accessories, textiles, apparel, etc. can market themselves as much as possible thanks to tourism. A tourist village is an asset based on rural potential, including all its characteristics and attractions. From the background that has been described, the author is interested in analyzing tourism potential. Therefore, the author raises the title "Community Participation in the Development of the Tanjung Balam Tourism Village, Siak Hulu District Kampar Regency Data analysis in this research completely uses descriptive writing techniques which combine stages of qualitative analysis according to the problem emphasis and research objectives. During the field data collection process, data from observations, interviews and document studies continues to be processed according to the principles of qualitative analysis. To confirm the research findings, the analysis stages for each type of data were completed collectively. Overall, the Tanjung Balam Tourism Village is able to combine natural beauty, cultural traditions, and active community involvement in building a tourist destination that is not only attractive to tourists but also has an economic, social and cultural impact on local residents. The success of developing the Tanjung Balam Tourism Village greatly influenced by the active participation of the local community, especially youth. Youth are also driving promotional activities through social media, especially Instagram, which is effective in expanding the reach of information about this tourist village. Kata kunci: Participation, Community, Development, Tourism Village